2014
DOI: 10.3892/mmr.2014.2772
|View full text |Cite
|
Sign up to set email alerts
|

Potential regulatory molecules in the human trabecular meshwork of patients with glaucoma: Immunohistochemical profile of a number of inflammatory cytokines

Abstract: Glaucoma occurs when there are imbalances between the production and the drainage of the eye liquid. The vast majority of the aqueous humor leaves the eye through the trabecular meshwork (TM). The cause of hypertonicity may be due to an alteration in the thickness of the TM. In the majority of cases the molecular changes that determine primary open‑angle glaucoma (POAG) are unclear. However, it has been hypothesized that the significant increase in the extracellular matrix (ECM) of the fibrillary bands in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 16 publications
3
35
1
2
Order By: Relevance
“…In the case of uveitis, a form of glaucoma called inflammatory, or uveitic, glaucoma can result from obstruction of drainage structures in the anterior segment as a secondary consequence of the ocular inflammation (Bodh et al , 2011; Siddique et al , 2013; Baneke et al , 2015). In the case of steroid-induced glaucoma, the steroids are generally thought to be deleterious, not by their action in reducing inflammation, but rather by acting directly to affect the drainage structures, among other things, by increasing extracellular matrix deposition by trabecular meshwork cells, which increases outflow resistance and consequently increased intraocular pressure (Clark et al , 1995; Tektas et al , 2011; Overby et al , 2014; Raghunathan et al , 2015; Taurone et al , 2015). This paradoxical relationship between inflammation and glaucoma (both inflammation and anti-inflammatory treatment can give you glaucoma), together with the absence of obvious large-scale lymphocyte infiltration into the retina (Yang et al , 2001; Tezel and Wax, 2004), have contributed to the generally held notion among clinicians that human glaucoma is not an inflammatory disease.…”
Section: Neuroinflammation In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of uveitis, a form of glaucoma called inflammatory, or uveitic, glaucoma can result from obstruction of drainage structures in the anterior segment as a secondary consequence of the ocular inflammation (Bodh et al , 2011; Siddique et al , 2013; Baneke et al , 2015). In the case of steroid-induced glaucoma, the steroids are generally thought to be deleterious, not by their action in reducing inflammation, but rather by acting directly to affect the drainage structures, among other things, by increasing extracellular matrix deposition by trabecular meshwork cells, which increases outflow resistance and consequently increased intraocular pressure (Clark et al , 1995; Tektas et al , 2011; Overby et al , 2014; Raghunathan et al , 2015; Taurone et al , 2015). This paradoxical relationship between inflammation and glaucoma (both inflammation and anti-inflammatory treatment can give you glaucoma), together with the absence of obvious large-scale lymphocyte infiltration into the retina (Yang et al , 2001; Tezel and Wax, 2004), have contributed to the generally held notion among clinicians that human glaucoma is not an inflammatory disease.…”
Section: Neuroinflammation In Glaucomamentioning
confidence: 99%
“…In addition, intrinsic up-regulation of complement molecules in RGCs (such as C1qa and C3) occurs early and mediates synaptic dysfunction. From Soto and Howell 2015 (Soto and Howell, 2014). …”
Section: Figurementioning
confidence: 99%
“…During glaucoma, macrophages in the TM produce cytokines, including IL‐6, IL‐1β, and TNF‐α, leading to an acute inflammatory response. These cytokines may induce ECM remodeling and alter cytoskeletal interactions in the TM (Taurone et al, ). IL‐6 has been seen to increase outflow facility in perfused anterior segments of porcine eyes (Liton et al, ), and IL‐8 modulates the permeability of the endothelial cells of SC (Alvarado et al, ).…”
Section: The Trabecular Meshworkmentioning
confidence: 99%
“…While it now is widely recognized that the autocrine and paracrine actions of factors secreted by the TM and SC cells influence their cellular characteristics with subsequent impact on AH outflow and IOP, 30,44–46 we lack comprehensive understanding of the identity of such factors. In this study, we showed that human TM cells express and secrete GDF-15.…”
Section: Discussionmentioning
confidence: 99%